2013
DOI: 10.3892/ijmm.2013.1294
|View full text |Cite
|
Sign up to set email alerts
|

Role of metallothionein in murine experimental colitis

Abstract: Abstract. Metallothioneins (MTs) are a family of cysteine-rich low molecular-weight proteins that can act as reactive oxygen species scavengers. Although it is known that the induction of MT expression suppresses various inflammatory disorders, the role of MTs in intestinal inflammation remains unclear. In this study, we investigated the effects of dextran sulfate sodium (DSS) administration in mice with targeted deletions of the MT-I/II genes. Acute colitis was induced by 2% DSS in male MT-I/II double knockou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 43 publications
4
33
0
Order By: Relevance
“…One gene that is highly overexpressed upon Smarcad1-KO in steady state and colitis is Mt1, coding for metallothionein. Metallothionein has been reported to protect against colitis in mouse models, but its role in this process requires further investigation [27,[69][70][71][72][73]. Another gene that is upregulated upon Smarcad1 deletion codes for Bambi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One gene that is highly overexpressed upon Smarcad1-KO in steady state and colitis is Mt1, coding for metallothionein. Metallothionein has been reported to protect against colitis in mouse models, but its role in this process requires further investigation [27,[69][70][71][72][73]. Another gene that is upregulated upon Smarcad1 deletion codes for Bambi.…”
Section: Discussionmentioning
confidence: 99%
“…These genes include Tlr4, encoding a Toll-like receptor (intestinal stem cells and organoid datasets); Itln1, a lectin receptor; defensins Defa22 and Defa26; Wdfy1 (positively regulates TLR3/4 signaling pathways [25]); and anti-microbial protein genes Ang4 [26], Reg3b, and Lyz1 (lysozyme). Mt1 that is significantly upregulated on Smarcad1 deletion plays an important role in the prevention of colonic mucosal inflammation in the dextran sodium sulfate (DSS)-induced mouse model of colitis [27]. Interestingly, Mt1 is not significantly upregulated in the small intestinal organoid culture upon Smar-cad1-KO, indicating that this upregulation may depend on some external cue, such as niche, microbiota, or immune cells (Fig.…”
Section: Smarcad1 Is Highly Expressed In the Intestinal Crypt And Itmentioning
confidence: 97%
“…MTs are a family of low molecular weight proteins containing cysteine residues, which enable high-affinity binding to monovalent and divalent heavy metal atoms. We previously reported that production of several inflammatory cytokines (TNF-α, IFN-γ, and IL-17) was significantly elevated in peritoneal macrophages derived from MT-I/II knockout mice [45], and that dextran sulfate sodium (DSS)-induced colonic inflammation as an animal model of UC was aggravated significantly in knockout mice [45]. Our results also confirmed a significantly higher expression of MT-I/II in the colonic mucosa of the DSS-induced colitis model using the real-time PCR analysis.…”
Section: Role Of Metallothioneins (Mts) In Intestinal Inflammationmentioning
confidence: 99%
“…For example, Tsuji et al reported that MTs had a protective effect in dextran sulfate sodium (DSS)-induced colitis. 32 More recently, exosomes enriched in MT-2 were found to be required for the suppression of inflammatory responses and for protection in DSS-induced colitis in mice. 33 In contrast, Tran et al showed that following DSS induction, MT-deficient mice displayed lower levels of inflammation than wild-type mice did.…”
Section: Introductionmentioning
confidence: 99%
“…An MT-specific monoclonal antibody has been used as a novel therapeutic in murine models of IBD. 34 The disparities regarding the protective or non-protective effects of MTs 19,32,35,36 may be attributed to a variety of factors, including (i) differences in dose levels and dose timing in chemically induced colitis, (ii) differences in the time points at which clinical measurements were made and tissue samples were collected following induction of colitis, and (iii) microbiome heterogeneity in mice strains housed in different animal facilities. 31 Thus, we need to better understanding the nuances of the MTs' complex functions and how these proteins influence the pathogenesis of IBD.…”
Section: Introductionmentioning
confidence: 99%